Modulation of Aggregation Behaviour of Amphiphlic Drug and Surfactant Mixture under the Influence of Neutral Polymer - Azum, Naved; Abdul Rub, Malik; M. Asiri, Abdullah; Aslam Parwaz Khan, Aftab; Khan, Anish; Bahadar Khan, Sher; M. Rahman, Mohammed (Asian Journal of Chemistry, 2014)
The interaction of non-ionic surfactant, Triton X-114 (TX-114) with amphiphilic drug i.e., imipramine hydrochloride (IMP) has been investigated by surface tension measurement in the absence and presence of hydroxypropyl methylcellulose (HPMC) polymer. In the presence of the HPMC the plots of surface tension versus concentration of TX-114 + IMP mixed system show interesting features (i.e., two break points). The two break points attributed to the occurrence of two kind of aggregation process. In the presence of HPMC, the first break is close to that in pure water, can be regarded as critical aggregation concentration (cac), whereas second one is 2-3 times higher than the first one and can be attributed to the polymer bound micelles. The interfacial and bulk behavior was investigated using various theoretical models of Clint, Rosen, Rubingh etc. Synergism was observed in all binary combinations in the micelle and at the interface with or without the HPMC. Various thermodynamic parameters have been calculated with the help of regular solution theory (RST) and pseudo phase model for micellization.